Cognitive strategies for excellence in tennis: The role of exergames (Sport and Exercise Psychology, 2025)
The concepts of proactive inhibition (anticipatory preparation to inhibit a response) and reactive inhibition (inhibition of a response that has already been initiated) are implicitly addressed in discussions of visual anticipation and action control among elite athletes. Neuroscientific studies suggest that the ventromedial prefrontal cortex is primarily involved in proactive inhibition, whereas the right inferior prefrontal cortex plays a key role in reactive inhibition. The superior performance observed in athletes, including tennis players, may result from a more effective integration of both mechanisms, thereby enhancing their capacity to anticipate and respond efficiently to complex stimuli. Considering this theoretical framework, the paper proposes a series of practical guidelines aimed at supporting the development and optimization of these cognitive processes through the use of specific exercises known as “exergames”, presented as a theoretical framework and not yet empirically tested. This methodological proposal, of a conceptual and proof-of-concept nature, aims to provide a starting point for future empirical studies and to guide training practices and performance enhancement strategies.
Keywords: Inhibitory control; Exergames,; Visual anticipation; Open-skill sports